Enhancing Web Development Education With Game-Based and Gamification Learning: A Study of Engagement, Motivation, and Performance - Ojonuba, Suzan Ejura; Turkmen, Guzin; Toker, Sacip (IEEE access, 2025)
Web development is a dynamic and complex subject in the computer science field that can be challenging to learn among higher education students. We investigated the impact of game-based learning and gamification on students' engagement, motivation, and performance in a web development course in this study. We tested 60 university students, who were expected to learn from a novice or beginner level. The experimental group used a gamified system, while the control group used a non-gamified system. All game elements in this study were grounded in self-determination theory (SDT), which suggests that intrinsic motivation increases when learners feel autonomous, competent, and connected, and flow theory, which emphasizes that when challenge and skill are balanced, learners are more likely to experience a state of flow. Quantitative and qualitative data were both collected and analyzed. Results showed that the gamified system positively impacted students' performance, compared to the non-gamified system. Interestingly, there was no significant difference in the engagement and motivation of the students. The findings of this study suggest that while the game elements addressed students' psychological needs, gamified learning outcomes depend not only on the inclusion of these game elements but also on individual learner differences such as prior game experience, learners' expectations of the gamified system and how well the designed system sustains engagement over time to overcome the novelty effect. In conclusion, these findings have significant implications for web development education and suggest that game-based learning and gamification are promising approaches for web development education.